Propriedades genéricas de sistemas hamiltonianos - Lemes, Ricardo Chicalé [UNESP] (2013)
In this work our goal is to prove the General Density Theorem which is an analogous result for hamiltonian vector fields of the Kupka-Smale Theorem. The General Density Theorem states that the set of hamiltonian vector fields on a symplectic manifold M that has the property H2-N is a residual subset of Xk H(M). We begin by stating the basic linear and nonlinear symplectic theory and then we study its connections with hamiltonian systems, proving some of the main theorems of the theory and other related results. Here we give special attention to topics like generic curves of symplectic matrices, generating functions of symplectic diffeomorphisms and their applications in the problem of the stability of eliptic fixed points of hamiltonian systems, which is partially solved using the Birkhoff Normal Form. After stating the necessary results, we begin to study some hamiltonian dynamics using one-parameter families of symplectic diffeomorphisms. We prove a result stated by Pugh and consider the problem of structural stability of a certain type of one-parameter family. Finally we prove the General Density Theorem using the notion of pseudotransversality given in Appendix C. This work is based on the lecture notes Lectures on Hamiltonian Systems of professor R. Clark Robinson